2020
DOI: 10.1007/s00520-020-05846-7
|View full text |Cite
|
Sign up to set email alerts
|

“Do I want to know it all?” A qualitative study of glioma patients’ perspectives on receiving information about their diagnosis and prognosis

Abstract: Purpose Glioma patients have poor prognosis. The amount of detail of disease-related information patients wish to receive is not known. The aim of this study was to explore glioma patients’ experiences and preferences regarding receiving information on diagnosis and prognosis. Methods Semi-structured interviews were performed with patients diagnosed with glioma. The interviews were analysed by qualitative content analysis without predefined categories by two independent coders. Results Ten women and 15 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“… 53 In our analysis, the crucial point seemed to be the individual understanding – by patients, relatives and staff – of what honest and truthful communication includes. Like Malmström et al and others illustrated, and was also shown here, this could differ widely per person 30 , 33 , 55 , 56 opening up the potential for conflict when individual understandings differ. Reflecting the communicational approach of our staff interviewees in context of the existing literature, their general approach seems to be in line with what is currently known about the communicational needs of patients and relatives.…”
Section: Discussionsupporting
confidence: 78%
“… 53 In our analysis, the crucial point seemed to be the individual understanding – by patients, relatives and staff – of what honest and truthful communication includes. Like Malmström et al and others illustrated, and was also shown here, this could differ widely per person 30 , 33 , 55 , 56 opening up the potential for conflict when individual understandings differ. Reflecting the communicational approach of our staff interviewees in context of the existing literature, their general approach seems to be in line with what is currently known about the communicational needs of patients and relatives.…”
Section: Discussionsupporting
confidence: 78%
“…The suggested procedure of this QPL use (i.e. provided by the oncologist, at initial consultations, in its long or short form as the oncologist feels is appropriate, patients' invitation to read it at home and to select questions they wish to discuss at a subsequent consultation) was designed to encourage patients to address questions of interest to them personally and in the time frame suiting their needs (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Złożoność potrzeb i preferencji pacjentów w zakresie informacji sprawia, że rola lekarza jest w tym aspekcie trudna. Pacjenci chcą znać prawdę na temat swojego obecnego sta- nu zdrowia, choć zakres pożądanych informacji jest różny [11,12]. Większość pacjentów preferuje otrzymywanie pełnej informacji dotyczącej swojej sytuacji oraz dalszego postępowania (50-70% pacjentów, w zależności od okoliczności) [13], jednak wielu chorych oczekuje informacji jedynie o niezbędnych elementach wymaganych do podjęcia odpowiednich działań, co może być uwarunkowane obawą przed otrzymywaniem złych wiadomości, które mogłyby sprawić przykrość zarówno im, jak i ich bliskim [14].…”
Section: Dyskusjaunclassified